ASESMEN POTENSIAL REVIEW PADA KARYAWAN CV BM DALAM PENGEMBANGAN SUMBER DAYA MANUSIA - Hamdi, Raspan; Sunarsih; Arifin; Alfina Tiur Mida Sitanggang; Putri Fatimah (Program Studi Psikologi Islam, 2024)
In order to effectively realize the company's vision and mission, one of the most important components is human resources. Employees are the most important asset in an organization so that each employee is required to work optimally based on their abilities. This research aims to measure the potential possessed by employees who take part in performance evaluations and to fulfill the self-development needs of employees at CV BM. The subject in this research was 1 person who was in the position of cutting & design coordinator. Data collection methods use psychological tests and interviews. Data analysis uses descriptive analysis and qualitative analysis. The results of the assessment show that the subject does not meet the potential standards expected in the position of cutting & design coordinator with a recommendation of